Distortion and dimensional deviation of Inconel 718 auxetic structures produced by DMLM (Journal of Additive Manufacturing Technologies, 2021)
Due to their geometrical shapes, auxetic structures expand laterally when stretched and contract laterally when compressed. These structures find their usages in different industries where high energy absorption, toughness, flexural rigidity or buckling under pure bending are required. Since additive manufactured parts have some amount of distortion and since this distortion has a great influence on mechanical properties of the final part, knowledge about distortion characteristics of thin-walled lattice structures manufactured by additive manufacturing is very important to better estimate and evaluate the mechanical behavior of these parts when used in industrial applications. For this purpose, this study focuses on distortion characteristics of IN718 re-entrant, anti-tetrachiral and honeycomb lattice structures manufactured by direct metal laser melting technology. The specimens with different geometries were scanned in two conditions: just after printing when parts are still on build plate and just after removing the specimens from build plate and splitting them into three pieces. Scanned data were compared with the original CAD model and finite element analysis.
Keywords: lattice structures; additive manufacturing; blue light scan; geometric deviation; distortion.